"Environmental Justice" and Persons with Disabilities in Israel - Feldman, Dina (Disability Studies Quarterly, 2007)
The decades of unsuccessful efforts to legislate and implement legislation in the area of accessibility for persons with disabilities in Israel have shown that in order to promote a social, geographical, ecological revolution in the lives of persons with disabilities there is a need for a relevant, attractive conception and language that will enable the Israeli society to make a paradigm shift in this matter. This article introduces the concept of "environmental justice", which was defined in the 1998 Aarhus Convention, as a meta-conception that might be helpful to advance its three main components pertaining to disability: 1) the right to environmental accessibility; 2) the right to information about citizens' rights; and 3) the right to take part in the decision-making process. This article describes how the three components of the "environmental justice" concept are presented in the UN Convention on the Rights of Persons with Disabilities and in the local legislation and implementation thereof in Israel, with an emphasis on the decisive contribution of the Equal Rights of Persons with Disabilities Law, 5758 — 1998. This article shows that Israeli society has already acknowledged the importance of the concept in legislation and through active participation by policy makers, organizations, and planning professionals a new vision of an accessible reality is being formed. However, Israel is still in the initial stages of implementation. Key elements and factors that will increase the probability of making this environmental-justice revolution happen include: the existence of an international convention; relevant new and comprehensive legislation and conceptions; an Israeli Equal Rights Commission; and an active civil society and committed urban planners